DEVELOPMENT OF WEB-BASED E-STUDENT WORKSHEET USING WIZER.ME ON THE TOPIC OF HYDROCARBON COMPOUND COMBUSTION IMPACT AT GRADE XI - Maisura, Cahya; Hanum, Latifah; Zulfadli, Zulfadli (Chimica Didactica Acta, 2024)
The Development of Web-Based E-Student Worksheet Using Wizer.me on the Topic of Hydrocarbon Compound Combustion Impact at grade XI. The combustion of hydrocarbon compounds is a critical topic in environmental chemistry that students must thoroughly comprehend. This research aims to analyze the feasibility of the developed E- Student Worksheet and describe the responses of teachers and students to the E- Student Worksheet on the topic of hydrocarbon compound combustion impact. The research method applied is research and development (RD) following the 4-D model, which includes defining, designing, developing, and disseminating. The study was conducted at Senior High School 1 Ingin Jaya, involving 20 students from grade XI IPA 2 as the research subjects. The research instruments consisted of a needs analysis sheet, E- Student Worksheet feasibility sheet by validators, teacher response sheet, student response sheet, and System Usability Scale (SUS) sheet. Validator evaluation indicated a feasibility of 95% with a "highly feasible" category. The results of the teacher response evaluation to the E- Student Worksheet showed an excellent response of 91%, similarly, the students showed an excellent response of 91.13%, and the System Usability Scale (SUS) evaluation scored 82.50, indicating a "good" category. Thus, it can be concluded that the web-based E- Student Worksheet using Wizer.me on the topic of hydrocarbon compound combustion impact is considered feasible to be used as an interactive teaching material with the utilization of IT in learning.